Looking Beyond AFTA: Prospects and Challenges for Interregional Trade - Myrna S. Austria; John Lawrence V. Avila (Philippine Institute for Development Studies (PIDS), 2001)
The world trading environment has witnessed the proliferation of regional trading arrangements during the last decade. This development was accompanied by the perceived threat that this may bring to the rules-based multilateral trading system. The ASEAN for one have not only reaffirmed their commitment to move forward beyond the ASEAN Free Trade Area and towards higher level of economic integration but also are looking at enhanced interaction and closer linkages with other regional groupings. This paper examines the prospects and challenges for expanding AFTA for inter-regional trade by first identifying the elements and principles that should govern such expansion for it to contribute towards realizing global-scale liberalization. Areas for inter-regional linkage are also identified highlighting the possible issues and conflicts that might arise considering the differing objectives and scope that AFTA has with the other trade blocs which it might want to develop an inter-regional linkage. Some probable arrangements for linking/expanding AFTA with other groupings or non-ASEAN countries are then explored, particularly those involving CER, the East Asian countries and the Andean Community.
Keywords: 330; World Trade Organization; liberalization; competitiveness; economic integration; import commodities; export commodities; regional integration; regional trading arrangements; interregional trade; open regionalism; transparency; modalities; subregional groupings; ASEAN Free Trade Area (AFTA); Closer Economic Relation; Andean Community; Regionale Wirtschaftsintegration; Freihandelszone; ASEAN-Staaten